2012
DOI: 10.1155/2012/691894
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Nitrification Kinetics and Microbial Community during Bioaugmentation of Activated Sludge with Nitrifiers Enriched on Sludge Reject Water

Abstract: This study used two laboratory-scale sequencing batch reactors (SBRs) to evaluate the shifts in nitrification kinetics and microbial communities of an activated sludge sewage treatment system (main stream) during bioaugmentation with nitrifiers cultivated on real sludge reject water (side stream). Although bioaugmentation exerted a strong influence on the microbial community and the nitrification kinetics in the main stream, there was 58% of maximum ammonia uptake rate (AUR) and 80% of maximum nitrite uptake r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Nitrosomonas spp., Nitrosospira spp., and Nitrosococcus spp. are abundant in AOB communities of activated sludge ; Nitrospira ‐like bacteria, rather than Nitrobacter spp., are the dominant nitrite oxidizers in WWTPs and natural ecosystems . The high sensitivity of AOB (e.g., Nitrosomonas europaea ) to AgNPs has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Nitrosomonas spp., Nitrosospira spp., and Nitrosococcus spp. are abundant in AOB communities of activated sludge ; Nitrospira ‐like bacteria, rather than Nitrobacter spp., are the dominant nitrite oxidizers in WWTPs and natural ecosystems . The high sensitivity of AOB (e.g., Nitrosomonas europaea ) to AgNPs has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…The results of the AUR tests obtained by different authors are summarized in Table 4. These values range from 1.65 [49] to 27.5 mg N/g VSS h [15]. The highest SAURs of 27.5 and 19 mg N/g VSS h were obtained by Obaja et al [15] and Dosta et al [45] during the treatment of wastewater with a high ammonia nitrogen content, liquid fraction of digested piggery wastewater, and centrifuged reject water from an anaerobic digester in lab-scale SBR reactors.…”
Section: Amount and Activity Of Nitrifying Bacteriamentioning
confidence: 89%
“…This shows that the hydrolysis improved the uptake of molasses by bacteria, so similar SNURs were obtained at a lower COD/NO 3 -N ratio. A low SNUR value of 0.43 mg N/g VSS h was determined by Yu et al [49] when treating synthetic domestic wastewater containing glucose in a lab-scale SBR reactor. Zhao et al [50], analysing the influence of three carbon sources on nitrogen transformation in an aerobic granular sludge system, also found that bacteria hardly used saccharides, whereas the nitrogen removal rate was the highest when using sodium acetate.…”
Section: Amount and Activity Of Nitrifying Bacteriamentioning
confidence: 93%
See 1 more Smart Citation
“…As the economic costs associated with treatment processes become more pertinent, the use of 'one-off' dosing may become less viable. The use of side-stream technologies is becoming increasingly common due to their advantages in terms of bacterial adaptation and use in long-term bioaugmentation applications (Krhutková et al, 2006;Smith et al, 2008;Yu, Peng and Pan, 2012).…”
Section: Discussionmentioning
confidence: 99%